Exploring leisure : an introduction into leisure studies - Beunders, Niek, ....-; Boers, Han, ....-; Leijten-Kupers, Esther, ....- (Leiden : ToerBoek, 2009)
Exploring Leisure is a book on leisure time and the leisure time industry. The book consists of two parts. The first part describes, analyses and explains leisure time and how it is spent. It shows how environmental factors influence leisure time, how leisure time – as we know it today – originated, and the course leisure time is taking under the influence of the factors mentioned. The second part discusses how behaviour in the leisure industry, and tourism in particular, affects the environment. Special attention is being paid to social, economic and ecological effects. Case studies and examples are provided to illustrate everyday practice.
Met index, lit. opg.
Keywords: Recreatie; Tijdsbesteding; Vrijetijdsbesteding -- Sociologie